Sexuality in the Middle East and North Africa contemporary issues and challenges - Ryan, J. Michael; Rizzo, Helen Mary (Syracuse University Press, 2024)
"This volume explores the often overlooked yet critical role that sexualities play in the MENA region"--
Keywords: Sexualität; Nordafrika; Naher Osten; Sex / Middle East; Sex / Africa, North; Sexual orientation / Middle East; Sexual orientation / Africa, North; Sexualité / Afrique du Nord; Aufsatzsammlung